Swine sarcoptic mange. II. Economic evaluation of alternative control strategies - Girotto, Ademir Francisco; Sobestiansky, Jurij; Lignon, Gilberto B.; Faccini, João L. H.; Mezacasa, Maximino L. (Pesquisa Agropecuaria Brasileira, 1995)
The aim of the paper was to compare economically three control methods of sarcoptic mange. The methods were: 1) strategic method (SM); 2) injectable product (IP); 3) spray product (SP). The SM was applied from 1982 to 1988 in a confined herd with 240 sows and 12 boards, while the cost of IP and SP were estimated assuming identical effects in terms of mange control. The costs of the treatments were calculated for each year for the herd and by animal. From 1982 to 1985 the SM presented the lowest total cost while from 1986 to 1988 the SP had small total cost. The SM, IP and SP had an increase of 312%, 1.04% and 6.24% respectively. The exam of "scrapings" of "EC" not always is available to the producers or the access is difficult. In these cases the spray product showed the indicated alternative.
Keywords: sarcoptic mange; confinement; reproduction animais; injectable product; spray product; herd